Peningkatan Self Management Melalui Program Telemonitoring Terhadap Kepatuhan Medikasi Pasien Congestive Heart Failure (CHF): A Literatur Review - Selvia B, Heni; Sjattar, Elly L; Madjid, Abdul (Universitas Tribhuwana Tunggadewi, 2022)
Congestive Heart Failure (CHF) is a chronic complex syndrome characterized by the inability of the heart to support Congestive Heart failure is a clinical syndrome characterized by shortness of breath, swelling of the ankles, and fatigue. One of the actions taken for the treatment is to improve self-management and patient medication adherence through a telemonitoring program. The study review's purpose was to identify the effect of a telemonitoring program in improving the self-management of congestive heart failure patients on medication adherence. The literature review used some electronic databases including Pubmed, Google Scholar, and ScienceDirect, and obtained seven articles that meet the inclusion criteria. The results showed that the telemonitoring program was effective in increasing medication adherence, blood pressure control adherence, improving medication regimens, reducing treatment costs, and improving self-management of patients with congestive heart failure. The telemonitoring program becomes an appropriate solution to enhance patient self-management on medication adherence as prevention and management of this disease. Telemonitoring programs were also known to reduce readmission of congestive heart failure patients to hospitals or clinics, reduce treatment costs, increase adherence to treatment regimens, and patient self-care management.